2018
DOI: 10.1097/id.0000000000000796
|View full text |Cite
|
Sign up to set email alerts
|

Acellular Dermal Matrix as a Barrier for Guided Bone Regeneration of Dehiscence Defects Around Dental Implants

Abstract: The presence of hard tissue dehiscence and thin periodontal biotype in the esthetic area is a challenge that can jeopardize function and aesthetic outcome of implants. Here, we present a successful simultaneous soft tissue and bone regeneration of dehiscence defects in the maxillary incisor region. The novelty of this case lies in the simultaneous bone regeneration and soft tissue augmentation and the use of acellular dermal matrix as a barrier for regeneration and biotype conversion around dental implants. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Acellular tissue ECM scaffolds are natural biological biomaterials with effective removal of cell components which are supposed to have immunogenicity to the host, while retaining the naturally occurring three‐dimensional (3D) structure with tissue‐specific origins of ECM structural proteins (collagens and elastin), specialized proteins (fibrillin, fibronectin, and laminin), proteoglycans (glycosaminoglycan, heparin sulfate, and chondroitin sulfate), and growth factors which are hard to be created synthetically (Cheng, Solorio, & Alsberg, ; Gupta, Mishra, & Dhasmana, ). So far, acellular tissue materials used for GBR include human dermal (Borges et al, ; de Andrade et al, ; Momen‐Heravi, Peters, Garfinkle, & Kang, ), human amnion (Li et al, ), bovine pericardium (Bai et al, ), and porcine pericardium (Hwang, Kim, Kim, & Lee, ) out of which only acellular dermal are put into clinical use, and others are still in preclinical research stages. Although tissue‐derived ECM materials are commonly used to repair non‐homologous anatomic sites, materials derived from site‐specific homologous tissues have been suggested to be more helpful for constructive tissue remodeling as compared to nonsite‐specific tissue sources (Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Acellular tissue ECM scaffolds are natural biological biomaterials with effective removal of cell components which are supposed to have immunogenicity to the host, while retaining the naturally occurring three‐dimensional (3D) structure with tissue‐specific origins of ECM structural proteins (collagens and elastin), specialized proteins (fibrillin, fibronectin, and laminin), proteoglycans (glycosaminoglycan, heparin sulfate, and chondroitin sulfate), and growth factors which are hard to be created synthetically (Cheng, Solorio, & Alsberg, ; Gupta, Mishra, & Dhasmana, ). So far, acellular tissue materials used for GBR include human dermal (Borges et al, ; de Andrade et al, ; Momen‐Heravi, Peters, Garfinkle, & Kang, ), human amnion (Li et al, ), bovine pericardium (Bai et al, ), and porcine pericardium (Hwang, Kim, Kim, & Lee, ) out of which only acellular dermal are put into clinical use, and others are still in preclinical research stages. Although tissue‐derived ECM materials are commonly used to repair non‐homologous anatomic sites, materials derived from site‐specific homologous tissues have been suggested to be more helpful for constructive tissue remodeling as compared to nonsite‐specific tissue sources (Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…( Siddiqui et al, 2017 ; Jin et al, 2018 ). Momen-Heravi et al (2018) applied ADM to repair peri-implant bone-cracking and found that new bone was formed around the bone defect area with fine effect of bone reconstruction.…”
Section: Specific Types Of Barrier Membranesmentioning
confidence: 99%
“…During this process, the alveolar ridge undergoes relevant changes, both in height and in thickness, which influence the possibility of installing the implants. Thus, the optimized processes of implantology and biomaterials allow the installation of implants in areas of thin bone thickness, width and height, with simpler surgeries and greater success rate and patient comfort [25].…”
Section: Molecular and Cellular Processesmentioning
confidence: 99%